High-Dimensional DNA Methylation Mediates the Effect of Smoking on Crohn’s Disease - Wang, Tingting; Xia, Pingtian; Su, Ping (Frontiers in Genetics, 2022)
Epigenome-wide mediation analysis aims to identify high-dimensional DNA methylation at cytosine-phosphate-guanine (CpG) sites that mediate causal effect of linking smoking with outcome Crohn’s disease (CD). Studies have shown that smoking has significantly detrimental effects on the course of CD. So we assessed whether DNA methylation mediates the association between smoking and CD. Among 103 CD cases and 174 controls, we estimated whether the effects of smoking on CD are mediated through DNA methylation CpG sites, which we referred to as causal mediation effect. Based on the causal diagram, we first implemented sure independence screening (SIS) to reduce the pool of potential mediators CpGs from a very large to a moderate number; then, we implemented variable selection with de-sparsifying the Lasso regression. Finally, we carried out a comprehensive mediation analysis and conducted sensitivity analysis. It adjusted for potential confounders of age, sex and blood cell type proportions to estimate the mediation effects. Smoking was significantly associated with CD under odd ratio (OR) of 2.319 (95% CI 1.603–3.485, P <0.001) after adjustment for confounders. Ninety-nine mediator CpGs were selected from SIS and then, seven candidate CpGs were obtained by de-sparsifying the Lasso regression. Four of these CpGs showed statistical significance, the average causal mediation effects (ACME) were attenuated from 0.066 to 0.126. Notably, three significant mediator CpGs had the absolute sensitivity parameters of 0.40, indicating that these mediation effects were robust even when the assumptions were slightly violated. Genes (BCL3, FKBP5) harboring these four CpGs were related to CD. These findings suggest that changes in methylation are involved in the mechanism by which smoking increases risk of CD.